2011
DOI: 10.1021/jm101421d
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Predicting P-Glycoprotein (ABCB1) Inhibition Using Molecular Interaction Fields

Abstract: P-glycoprotein (Pgp or ABCB1) is an ABC transporter protein involved in intestinal absorption, drug metabolism and brain penetration, and its inhibition can seriously alter a drug's bioavailability and safety. In addition, inhibitors of Pgp can be used to overcome multidrug resistance. Given this dual-purpose, reliable in silico procedures to predict Pgp inhibition are of great interest. A large and accurate literature collection yielded more than 1200 structures; a model was then constructed using various MIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 104 publications
3
124
0
3
Order By: Relevance
“…“cell death of leukaemia cell lines”, “apoptosis” and “transport of cyclosporine”. Cyclosporine represents a well-known inhibitor of P-glycoprotein/ ABCB1 4647 and up-regulated P-glycoprotein/ABCB1 expression leads to increased cyclosporine efflux48. ABCB1 influenced a number of other biological functions and pathways, and PXR/RXR activation was among these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…“cell death of leukaemia cell lines”, “apoptosis” and “transport of cyclosporine”. Cyclosporine represents a well-known inhibitor of P-glycoprotein/ ABCB1 4647 and up-regulated P-glycoprotein/ABCB1 expression leads to increased cyclosporine efflux48. ABCB1 influenced a number of other biological functions and pathways, and PXR/RXR activation was among these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, medium-size compounds are able to inhibit only NorA. (3) A previous analysis 18 concluded that at least one polar feature (HB accepting group) is necessary for binding with Pgp. Here we confirm this hypothesis for both the proteins.…”
mentioning
confidence: 99%
“…In addition, from the point of view of early absorption, distribution, metabolism, and excretion (ADME) prediction of therapeutic agents, various computational prediction models have been reported for ligand interactions with P-gp. 2,[4][5][6][7][8][9][10] In general, a P-gp substrate seems to be lipophilic or amphiphilic, having a large size or molecular volume, electronegative groups and hydrogen bonding groups. 11) Although X-ray structures of the complex of mouse P-gp with enantiomeric cyclic peptide inhibitors have been reported previously by Aller et al in 2009, 12) the mechanism of P-gp substrate/inhibitor recognition is complicated and still poorly understood.…”
Section: Introductionmentioning
confidence: 99%